2020
DOI: 10.3390/app10228216
|View full text |Cite
|
Sign up to set email alerts
|

Determining Risk Factors for the Development of Temporomandibular Disorders during Orthodontic Treatment

Abstract: Temporomandibular disorders (TMD) represent a complex disease with a multifactorial etiology. Despite several studies on the subject, a causal relationship between orthodontic treatment and different forms of TMD has not been established. The aim of this study was to analyze the effect of orthodontic treatment on two aspects of TMD: myofascial pain and disc displacement. This retrospective cohort study followed 224 orthodontic adult patients at three points in time: before treatment (T0), immediately after tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In-depth analysis was performed on 19 papers, with the last 8 being excluded. Eventually, this literature review included 11 papers [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In-depth analysis was performed on 19 papers, with the last 8 being excluded. Eventually, this literature review included 11 papers [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cases, it could persist. 14 Tecco et al showed the trigger points on masseter and temporal muscles, clicking sound, muscle, and joint pain significantly decreased after the orthodontic treatments. These findings fathomed the result of the maxillary expansion to align the teeth which allowed the mandible to move forward and settled in the natural decompressive position of the TMJs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested further studies were still needed to conclude the direct correlation between both. 14 Not much different for the hormonal factors, some studies that put gender variable into their work, concluded it did not significantly relate to TMD. 10,11 Meanwhile some other studies found females experienced TMD four times more often than males, so far they only suspected testosterone hormone played the role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations